2002
DOI: 10.1096/fj.02-0145fje
|View full text |Cite
|
Sign up to set email alerts
|

Reduced tumor growth, experimental metastasis formation, and angiogenesis in rats with a hyperreactive dopaminergic system

Abstract: Outgrowth of solid tumors requires blood supply to the tumor. Tumor angiogenesis is dependent on the interplay between tumor-derived angiogenic factors and stromal cells. Recently, it has been shown that the neurotransmitter dopamine is a potent inhibitor of VEGF-induced angiogenesis. Moreover, there is evidence that patients with schizophrenia have a hyperreactive dopaminergic system and are relatively protected from cancer. We hypothesized that hyperreactivity of the dopaminergic system is related to reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 47 publications
(77 reference statements)
1
38
0
3
Order By: Relevance
“…Furthermore, tumour-derived VEGF promotes angiogenesis and tumour growth but this mechanism is attenuated by dopamine. 48,49 Cytoskeletal regulation In addition to calpain small subunit, expression changes in other genes associated with modulation of the actin cytoskeleton and microtubule structure were identified including ELMO1, WASF1, SEPT8 and OLFM1, which is a confirmed interactor with the schizophrenia-associated gene, DISC-1 (which in turn is a modulator of nerve terminal function). Actin is a major cytoskeletal protein found both pre-and postsynaptically and the modulation of actin dynamics by the genes described here may be linked to cytoarchitectural changes associated with synaptic modulation 50 The WASF1 downregulation observed is of particular interest as Kim et al 51 showed it to be a key regulator of actin-dependent morphological processes in mouse neurons.…”
Section: Signal Transductionmentioning
confidence: 99%
“…Furthermore, tumour-derived VEGF promotes angiogenesis and tumour growth but this mechanism is attenuated by dopamine. 48,49 Cytoskeletal regulation In addition to calpain small subunit, expression changes in other genes associated with modulation of the actin cytoskeleton and microtubule structure were identified including ELMO1, WASF1, SEPT8 and OLFM1, which is a confirmed interactor with the schizophrenia-associated gene, DISC-1 (which in turn is a modulator of nerve terminal function). Actin is a major cytoskeletal protein found both pre-and postsynaptically and the modulation of actin dynamics by the genes described here may be linked to cytoarchitectural changes associated with synaptic modulation 50 The WASF1 downregulation observed is of particular interest as Kim et al 51 showed it to be a key regulator of actin-dependent morphological processes in mouse neurons.…”
Section: Signal Transductionmentioning
confidence: 99%
“…This estimate is called the central dopaminergic index, which is significantly upregulated in schizophrenic patients (Chang et al, 1990;Amin et al, 1995). The present results that dopamine, via its effect on Treg, can lead to an increased ability to mount T-cell response to self-antigens, coupled with the known participation of autoimmune T-cells in fighting off cancer (Teunis et al, 2002) and the increased plasma dopamine levels in schizophrenic patients, might explain the relatively low incidence of cancer development observed in patients with schizophrenia (Dummer et al, 2002).…”
Section: Discussionmentioning
confidence: 61%
“…Basu and associates demonstrated that at non-toxic levels, dopamine administration inhibited the angiogenic functions of VEGF via the D2-receptor to induce endocytosis of VEGF receptor 2 on endothelial cells thereby preventing VEGF binding, receptor phosphorylation, and subsequent signaling steps [92]. Teunis and colleagues found that both tumor size and vessel density were lower in rats with a hyperactive dopaminergic system [91]. All these findings suggest a link between dopaminergic activity, angiogenesis, and tumor development.…”
Section: Other Stress Mediatorsmentioning
confidence: 99%
“…The inhibitory effect of dopamine is thought to occur through the dopamine receptors on the tumor cell surface or by auto-oxidation of dopamine creating the generation of reactive oxygen species. Additionally, dopamine may have anti-angiogenic properties and has been shown to inhibit cancer growth in several in vivo experimental models [90,91]. Basu and associates demonstrated that at non-toxic levels, dopamine administration inhibited the angiogenic functions of VEGF via the D2-receptor to induce endocytosis of VEGF receptor 2 on endothelial cells thereby preventing VEGF binding, receptor phosphorylation, and subsequent signaling steps [92].…”
Section: Other Stress Mediatorsmentioning
confidence: 99%